1999
DOI: 10.1128/jcm.37.9.2872-2876.1999
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of PCR, Culture, and Direct Fluorescent-Antibody Testing for Detection of Bordetella pertussis

Abstract: We prospectively compared the performance of culture, direct fluorescent-antibody testing (DFA), and an in-house-developed PCR test targeting the repeated insertion sequence IS481 for the detection of Bordetella pertussis in nasopharyngeal swab specimens. We tested 319 consecutive paired specimens on which all three tests were performed. A total of 59 specimens were positive by one or more tests. Of these, 5 were positive by all three tests, 2 were positive by culture and PCR, 16 were positive by PCR and DFA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(33 citation statements)
references
References 25 publications
1
30
0
2
Order By: Relevance
“…Several studies have demonstrated that molecular methods are far more sensitive than classical culture-based methods in identifying bacterial species. 38,39 However, in a recent study on feline bile, DNA sequencing was only able to identify bacteria in 1 bile sample for which bacteria had not already been identified with bacterial cultures. f Thus, although it appears desirable to expand this study by molecular methods, the latter study suggests that positive samples may not be more frequently detected by molecular methods.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that molecular methods are far more sensitive than classical culture-based methods in identifying bacterial species. 38,39 However, in a recent study on feline bile, DNA sequencing was only able to identify bacteria in 1 bile sample for which bacteria had not already been identified with bacterial cultures. f Thus, although it appears desirable to expand this study by molecular methods, the latter study suggests that positive samples may not be more frequently detected by molecular methods.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its remarkably enhanced sensitivity, PCR amplification and detection of IS481 insertion sequences in the B. pertussis genome has replaced direct fluorescent-antibody (DFA) methods and culture as the "gold standard" method for detection of this upper respiratory pathogen from nasopharyngeal secretions. A comprehensive, seminal study by Loeffelholz and colleagues (19) demonstrated that the sensitivities of conven- Fig. 1a.…”
Section: Testing Methods For Selected Bacterial Agents Of Emerging Anmentioning
confidence: 99%
“…Diagnosis of pertussis infection is best performed through polymerase chain reaction assay (sensitivity, 94%; specificity, 97%) or through direct fluorescent antibody testing (sensitivity, 52%; specificity, 98%). Nasal swab cultures (sensitivity, 15%; specificity, 100%) are routinely performed; however, they have high false negative rates and take 7 to 12 days to yield results [33]. Physicians in the United States are legally required to report cases of pertussis to state public health departments [26].…”
Section: Secondary Preventionmentioning
confidence: 99%